Therapeutic art: Fostering emotional balance in homemakers - Ulya, Syafira Rizka; Syarifah, Nailatus; Prastika, Fara Okta; Purwandari, Eny (Community Empowerment, 2025)
Rapid technological advancements and societal changes significantly impact family life, particularly in child-rearing. Parents often face emotional challenges that can affect parenting styles and children's psychological development. This activity provided therapeutic art training to 18 homemakers in Jayan Village, Boyolali, to improve emotion regulation. Utilizing the Participatory Action Research (PAR) method, the training comprised three stages: planning, implementation, and evaluation. Results demonstrated increased parental awareness of emotion regulation and the effectiveness of therapeutic art in stress management. Through this activity, participants were able to channel both positive and negative feelings, thereby helping to prevent the accumulation of emotions that could have detrimental effects later on.